2019
DOI: 10.1159/000502891
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Light Therapy in the Treatment of Seasonal Affective Disorder: A Meta-Analysis of Randomized Controlled Trials

Abstract: <b><i>Background:</i></b> Bright light therapy (BLT) has been used as a treatment for seasonal affective disorder (SAD) for over 30 years. This meta-analysis was aimed to assess the efficacy of BLT in the treatment of SAD in adults. <b><i>Method:</i></b> We performed a systematic literature search including randomized, single- or double-blind clinical trials investigating BLT (≥1,000 lx, light box or light visor) against dim light (≤400 lx) or sham/low-density ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 73 publications
6
55
0
2
Order By: Relevance
“…Bright light therapy is an effective treatment for symptomatic seasonal depression 75 . The recurrent pattern of this subtype of depression provides a unique opportunity to examine preventive strategies.…”
Section: Clinical Subtypesmentioning
confidence: 99%
“…Bright light therapy is an effective treatment for symptomatic seasonal depression 75 . The recurrent pattern of this subtype of depression provides a unique opportunity to examine preventive strategies.…”
Section: Clinical Subtypesmentioning
confidence: 99%
“…We used the entire SIGH-SAD questionnaire as primary measure, since this is the current benchmark for assessment of depression severity in light therapy trials. 63 We chose the original 17-item HAM-D questionnaire as a secondary measure, since it is more commonly used in clinical practice and research. Blinded assessors conducted the SIGH-SAD interviews (including HAM-D questions) by telephone weekly in the intervention period and at follow-up.…”
Section: Primary and Secondary Outcome Measuresmentioning
confidence: 99%
“…In a recent meta-analysis, Nussbaumer-Streit et al (2019) found that the efficacy and safety of melatonin for prevention of SAD cannot be conclusively supported, owing to a lack of controlled clinical trials. Likewise, Pjrek et al (2020) remark that evidence for BL therapy comes from methodologically heterogeneous studies with small-tomedium sample sizes, but conclude that BL therapy is effective. Others take issue with the lack of effective controls in BL therapy studies (Golden et al, 2005), and larger high-quality clinical trials are clearly needed.…”
Section: The Role Of Lightmentioning
confidence: 99%